PET TAC and Resting state EEG-fMRI in Evaluation of the Ability to Understand and want in Patients Affected by Dementias with Neuro-psychiatric Disorders and other Mental Disorders - Avesani, Mirko; Beghini, Graziella; Agnoli, Francesco; Franchi, Lucilla; Vianello, Camilla; Zamparelli, Assunta; Trevisan, Cristiana; Scarpa, Cinzia; Siliprandi, Nicola; Camicia, Manuela; Adami, Laura; Rossi, Laura; et al. (Archives of Case Reports, 2024)
Introduction: We strongly believe that RS-fMRI using independent component analysis (ICA) must be considered as a technique to be systematically used in the near future, as positron emission tomography (PET TC) is today. Unfortunately, this technique is not yet used in Italy because, despite the studies just summarized, it is considered “experimental” and not routine without reasonable justification! Aim of the Study: We present two cases studied with these techniques, after the informed consent obtained by the patients 1) A young woman from Sicily, in whom an RS-fMRI revealed her severe personality disorder, was found capable of insight and strong-willed and was therefore found guilty by the criminal court of the murder of her young son, with a strange motive: RS-fMRI cannot be considered part of the assessment because it is so far considered experimental. PET-TAC was also classified as routine in Italy after a long legal discussion. We hope that all these studies, which are now summarized in this review, will be considered useful, at least in Europe, when a judge has to decide whether to sentence a person with psychological or psychiatric problems or to consider them as a person to be treated in a specific residential home (called REMS in Italy). 2) Another woman from Bergamo, after having killed a neighbor of hers, was, instead, considered not guilty because of her inability to want to kill him, and so admitted to a particular structure (REMS: residence to execution of security measures) to treat her problem, front temporal dementia, with a severe neuropsychiatric disorder (NPS), diagnosed after the crimen was fulfilled. Conclusions: These two interesting cases demonstrate that in Italy nowadays, we do not have a homogeneous methodology to investigate the ability to understand and want, limiting the study only to personality tests. Here we describe new techniques that may help in this objective.